2021
DOI: 10.3390/pathogens10060720
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Levels in the Serum of Persons with Onchocerciasis-Associated Epilepsy: A Case-Control Study

Abstract: Onchocerciasis-associated epilepsy (OAE) is a devastating childhood disorder occurring in areas with high Onchocerca volvulus transmission. Despite epidemiological evidence showing the association between O. volvulus and epilepsy, the underlying mechanism remains unknown. Since high levels of serotonin are known to induce seizures, we investigated serotonin levels in persons with OAE and controls selected from the Democratic Republic of Congo. Serum serotonin levels were determined by ELISA in 19 persons with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…In the context of the role of OV in the pathogenesis of NS, it was found that epilepsy was associated with low serotonin levels (β = −2.967; p = 0.017). High levels of serotonin (a neuromodulator) therefore do not seem to be involved in the pathogenesis of OAE (including NS) [35]. This study was of average and poor quality according to the NOS and DCP scales, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of the role of OV in the pathogenesis of NS, it was found that epilepsy was associated with low serotonin levels (β = −2.967; p = 0.017). High levels of serotonin (a neuromodulator) therefore do not seem to be involved in the pathogenesis of OAE (including NS) [35]. This study was of average and poor quality according to the NOS and DCP scales, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Although several epidemiological studies have shown a potential association between epilepsy and infection with the filarial nematode O. volvulus in different African countries [2][3][4][5], the mechanisms inducing pathogenesis are still unknown. Within our study, we aimed to investigate different immune parameters, neurodegeneration markers and the O. volvulus biomarker NATOG in patients from endemic areas presenting with nodding syndrome or other epilepsy disorders with or without a concomitant O. volvulus infection, determined via PCR of skin snips.…”
Section: Discussionmentioning
confidence: 99%
“…OAE seems to start without any obvious cause, in previously healthy children, between the ages of 3-18 years. Cases are reported in areas of high ongoing or past onchocerciasis transmission in various regions of sub-Saharan Africa including Uganda, Tanzania, the Democratic Republic of the Congo, the Central African Republic, Cameroon and South Sudan [2][3][4][5]. OAE has public health implications in endemic regions; with more than 381,000 people estimated to be affected in 2015 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this test cannot not discriminate between individuals who developed epilepsy, NS or remained healthy. Contrary to the application of the OAE criteria [7][8][9][10][11][12][13][14][15][16][17], studies investigating epilepsy/NS in context of an active OV infection are scarce. It has been shown that immunity and metabolism are strongly modulated in individuals who are actively infected with filarial nematodes (or helminths) in comparison to individuals that have cleared the infection [18][19][20].…”
mentioning
confidence: 99%